Power and colour Doppler ultrasonography for evaluation of the ovarian and uterine haemodynamics of infertile mares - K. H. El-Shahat; A. Abo El-Maaty; M. Helmy; Y. El Baghdady (Bulgarian Journal of Veterinary Medicine, 2020)
The present study was undertaken to investigate the haemodynamics of the ovary and uterus in infer-tile mares using power and colour Doppler ultrasonography. Forty-seven Arabian mares were handled in the current work through several examinations. Based on the breeding history complaints, physical, vaginal examination and Doppler examination, 12 mares were found to be suffering from abnormal ovarian structures (Experiment I). In addition, nine mares with normal cyclic activity were kept as control. Another 16 mares were found to suffer from abnormal uterine conditions and 10 mares with normal uterine findings served as control (Experiment II). Blood flows to the anovulatory follicle, ovarian inactivity, granulosa cell tumour were compared to those to the dominant follicle and luteal blood flow. Uterine blood flow of cysts, abnormal uterine fluids (endometritis) during estrus and diestrus were compared to normal uterine vascularisation during estrus, diestrus and post-mating. Results showed that granulosa cell tumour had the highest red colour blood flow and total colour blood flow area. Blue colour blood flow area of the corpus luteum was higher compared to the dominant follicle and inactive ovary. Uteri with uterine cyst and abnormal uterine fluids during estrus of infertile mares had high red colour blood flow, blue colour blood flow and power blood flow areas compared to normal uterus during estrus. It could be concluded that Doppler ultrasound could distinguish between normal ovaries with normal or abnormal structures. Moreover, the increased uterine blood flow area of mares with abnormal fluids in their uteri (endometritis) and uterine cysts could be distinguished by comparison to the normal uterine blood flow during estrus.